Effect of Two Different Methods Reducing Body Mass (Rapid and Medium Rapid) on Professional Wrestlers' Changes in Body Composition and Force - Birutė Matulevičiūtė; Renata Žumbakytė Šermukšnienė; Pranas Mockus; Agnė Bieliūnaitė (Lithuanian Sports University, 2018)
Research background and hypothesis. Wrestlers often want to reduce body mass during a short period of time. According  to  literature,  it  is  important  not  to  change  body  composition  when  reducing  body  mass.  It  has  been intended to examine muscle force changes when reducing body mass rapidly and averagely rapidly. Research aim was to estimate the effect of methods reducing body mass (rapid, averagely rapid) on wrestlers' changes in body mass components and force. Research methods. Groups of research participants: one - wrestlers who did not reduce body mass (n = 47), two  -  wrestlers  who  reduced  body  mass  rapidly  (n  =  16),  three  -  wrestlers  who  reduced  body  mass  averagely rapidly (n = 9). Muscle force (dynamometer MMT) and mass components (bio-impedance method Tanita 300) were estimated before and after reducing body mass. Research results.  Before reducing body mass (rapidly, averagely rapidly) wrestlers' body mass was greater (p < 0.05) than after reducing it. Wrestlers lost 4.5% of body mass when reducing it rapidly (24-72 hours), when averagely rapidly (72 hours - 2 weeks) - 4.03%. After reducing body mass fat free body mass decreased tendentiously. Using rapid method, wrestlers' force of both legs diminished (p < 0.05), when using averagely rapid method, force of left leg diminished (p < 0.05). Force of arms decreased (p < 0.05) after reducing body mass by both methods. Discussion and conclusions. Subjects used aggressive method of reducing body mass. They need appropriate training about athlete nutrition, optimal reduced body mass. Tendentious decrease in free body mass shows decrease in muscle force. Force  in  arms  and  legs  significantly  decreased  for  wrestlers  using  rapid  and  averagely  rapid  methods  for reducing body mass. Keywords:  reducing body mass, mass components, change in force, judo.